Tree performances of eight rootstocks grafted with ‘Šumadinka’ sour cherry - Milošević, Tomo; Milošević, Nebojša; Moreno, María-Angeles; Mladenović, Jelena (Spanish Journal of Agricultural Research, 2024)
Aim of study: This study was conducted to determine the suitability of seven clonal and one seedling rootstocks for grafting of sour cherry cv. ‘Šumadinka’ trough early tree growth, precocity, productivity and fruit quality.Aim of study: To evaluate the suitability of seven clonal rootstocks and one seedling rootstocks for grafting the sour cherry cv. ‘Šumadinka’ based on early tree development, precocity, productivity and fruit quality.Area of study: A sour cherry orchard in village Prislonica, Serbia, near Čačak city.Material and methods: The sour cherry cultivar ‘Šumadinka’ was grafted onto Colt, MaxMa 14, Krymsk 6, Adara, Cigančica, Gisela 5, Gisela 6 and Myrobalan rootstocks. Standard and validated procedures were used to measure tree growth, productivity (from 2017 to 2020), leaf area, fruit physical properties and fruit chemical composition (from 2019 to 2020).Main results: Significant differences were observed among rootstocks in leaf and petiole dimensions, leaf area, tree vigour, yield, fruit size, soluble solids content, titratable acidity, sugars and vitamin C contents, ripening and sweetness indexes. Trees grafted on Adara exhibited the highest tree vigour, while those on Gisela 6 produced the largest fruit size. On the other hand, Colt trees generally displayed the highest sugar content and sweetness index. Adara also showed improvements in fruit quality characteristics, whereas the properties associated with Myrobalan received the lowest evaluation scores.Research highlights: Adara rootstock demonstrated good adaptability to heavy and acidic soil conditions in Serbia, even though it was originally selected for cherry cultivation in heavy, waterlogged, and calcareous soils in Spain. This adaptability likely contributed to its higher vigour, yield, yield efficiency and good fruit quality.